Effects of different plant communities on fine particulate matter concentrations in green areas around Quancheng Road, Jinan - Mi, Hanwen (Technium EcoGeoMarine, 2022)
To study the effect of different plant communities on fine particulate matter PM2.5 and PM10 concentrations in green areas attached to urban roads is an important basis for improving the air pollution control function of urban green areas and optimizing the configuration of green areas, and it can provide an optimal solution for plant configuration selection. In this paper, the intersection of Quancheng Road and the front street of the provincial government in the Lixia District of Jinan City was selected as the research object, which has certain research value because of its important political and commercial functions and therefore has a large flow of people and vehicles. The CEM DT-9880 particle counter was used to measure the concentration of fine particulate matter at 1m and 2m height, respectively, and to analyze and compare the effect of different plant communities on fine particulate matter concentration and dust removal ability. The design optimization strategy of road accessory green space was proposed to regulate and improve the fine particulate matter.